Digital Consumer Literacy as a Determinant of Trust in Digital Economic Transactions - Maharani, Leonita; Undartik, Sri; Aziz, Muhandis Difa'iy (PT. Anagata Sembagi Education, 2026)
This study examines the role of digital consumer literacy as a determinant of trust in digital economic transactions within the Indonesian context. The rapid expansion of the digital economy has increased reliance on online platforms, yet concerns regarding security, fraud, and data privacy continue to challenge consumer trust. Digital literacy is conceptualized as a cognitive and protective capability that enables consumers to evaluate information, understand digital risks, and engage safely in online transactions. This research employs a quantitative explanatory design using survey data collected from consumers who have conducted digital transactions in the past six months. Data were analyzed using Structural Equation Modeling (SEM) to assess the validity of constructs and to test the structural relationship between digital consumer literacy and trust. The findings indicate that digital consumer literacy has a positive and statistically significant effect on trust in digital economic transactions, with moderate explanatory power. Consumers with higher levels of digital literacy demonstrate stronger perceptions of platform integrity, security, and reliability. The discussion highlights that digital literacy reduces perceived risk and enhances confidence in digital systems. In conclusion, digital consumer literacy significantly contributes to the formation of trust and should be strengthened through integrated policy and educational strategies to support sustainable digital economic participation.